Metabolic and molecular mechanisms of spine color formation in Chinese red chestnut - Qiao, Qian; Gao, Yun; Liu, Qingzhong (Frontiers in Plant Science, 2024)
The spines of Chinese red chestnut are red and the depth of their color gradually increases with maturity. To identify the anthocyanin types and synthesis pathways in red chestnut and to identify the key genes regulating the anthocyanin biosynthesis pathway, we obtained and analyzed the transcriptome and anthocyanin metabolism of red chestnut and its control variety with green spines at 3 different periods. GO and KEGG analyses revealed that photosynthesis was more highly enriched in green spines compared with red spines, while processes related to defense and metabolism regulation were more highly enriched in red spines. The analysis showed that the change in spine color promoted photoprotection in red chestnut, especially at the early growth stage, which resulted in the accumulation of differentially expressed genes involved in the defense metabolic pathway. The metabolome results revealed 6 anthocyanins in red spines. Moreover, red spines exhibited high levels of cyanidin, peonidin and pelargonidin and low levels of delphinidin, petunidin and malvidin. Compared with those in the control group, the levels of cyanidin, peonidin, pelargonidin and malvidin in red spines were significantly increased, indicating that the cyanidin and pelargonidin pathways were enriched in the synthesis of anthocyanins in red spines, whereas the delphinidin pathways were inhibited and mostly transformed into malvidin. During the process of flower pigment synthesis, the expression of the CHS, CHI, F3H, CYP75A, CYP75B1, DFR and ANS genes clearly increased, that of CYP73A decreased obviously, and that of PAL, 4CL and LAR both increased and decreased. Notably, the findings revealed that the synthesized anthocyanin can be converted into anthocyanidin or epicatechin. In red spines, the upregulation of BZ1 gene expression increases the corresponding anthocyanidin content, and the upregulation of the ANR gene also promotes the conversion of anthocyanin to epicatechin. The transcription factors involved in color formation included 4 WRKYs.